Psicanálise como arqueologia do sujeito, em Paul Ricoeur - Eser Tecio Pacheco (2001)
This thesis attempts to explore the fruitfulncss of the term "archeology of the subject", used by Paul Ricoeur to define the philosophical place of psychoanalysis, in "De L'inierpreiation: Esscii sur Freiui" (1965). Initially, some relevant information on the biography and bibliography of the French philosopher are provided, with an emphasis on the emergent period of the work in question. There is also a discussion of the hermeneutic perspective, with a brief review of the history of this perspective, calling attention to the contributions of Shleiermachcr, Dilthey, Heidegger, and Gadamer, and to how the questions they raised had repercussions in Ricoeur's tiiought. There follows Ricoeur's response to the question of the epistemological status of psychoanalysis, it being defined as a mixed energetic and hermeneutic discourse. Finally, the concept of "archeology of the subject" is analyzed, emphasizing Ricoeur's project of arriving, by way of hermeneutics, at a "concrete refiection" produced with the aid of Freudian thought